Mealworm hydrolysate ameliorates dexamethasone-induced muscle atrophy via sirtuin 1-mediated signaling and Akt pathway - Sung-Min Kim; Jong-Yeon Kim; Eun-Min Jun; Varun Jaiswal; Eun-Jung Park; Hae-Jeung Lee (npj Science of Food)
Abstract Loss of skeletal muscle mass and strength can result from various factors, including malnutrition, glucocorticoid usage, and diseases. The mealworm (Tenebrio molitor larvae) is an edible insect gaining popularity as an alternative protein-rich diet. Mealworms are expected to help alleviate muscle atrophy based on their rich, high-quality protein and peptide content, but it remains unclear whether mealworms ameliorate muscle loss. This study aimed to investigate the potential of mealworm hydrolysate (MH) in mitigating dexamethasone (DEX)-induced muscle atrophy and to elucidate the underlying mechanisms. MH ameliorates muscle atrophy by activating sirtuin 1 (SIRT1) and Akt, reducing muscle-specific RING finger protein-1 and atrogin-1 expression, and inhibiting apoptosis in DEX-treated C2C12 cells. Additionally, MH significantly increased the muscle mass, grip strength, and muscle fiber cross-sectional area by activating SIRT1 and Akt in DEX-treated rats. These findings suggest that MH has the potential in alleviating dexamethasone-induced muscle atrophy.